Effects of parecoxib after pancreaticoduodenectomy: A single center randomized controlled trial. (June 2021) - Liu, Guangnian; Ma, Yongsu; Chen, Yiran; Zhuang, Yan; Yang, Yinmo; Tian, Xiaodong
Abstract: Background: Parecoxib, a selective cyclooxygenase-2 inhibitor, is a potential alternative analgesic to reduce opioid consumption after Pancreaticoduodenectomy (PD). Further, the safety and efficacy of long-term use of parecoxib for patients after PD remain a major concern. Materials and methods: In this single-center, randomized clinical trial, 134 patients undergoing open PD were randomized into the parecoxib group (group P) and control group (group C) at a 1:1 ratio. Besides a routine patient-controlled epidural analgesia (PCEA) until 3 days postoperatively for both groups, patients in group P (n = 68) received parecoxib (40 mg, intravenously, Q 12 h) for the first 5 postoperative days and were encouraged to receive opioid analgesics to control severe pain as needed. Patients in group C (n = 66) received on-demand opioid analgesics (pethidine or morphine) postoperatively. The primary outcomes included the effectiveness of parecoxib in controlling pain (measured using the visual analog scale (VAS)) and reduction of opioid use (measured as accumulated doses). Secondary outcomes included the postoperative recovery process, rate of postoperative complications, and the anti-inflammatory effect of parecoxib. Results: The VAS scores were not significantly different between the two groups. The number of doses of opioids for patients in group P (3.2 ± 0.3 doses) was significantly lower than in group C (8.5 ± 0.4 doses) (p = 0.0007). The incidence of opioid-related side effects was significantly lower in group P than in group C (p = 0.001). There were no significant differences in postoperative complications or readmission rates between the two groups. The postoperative time to first pass flatus, time to first mobilization out of bed, and time of removal of nasogastric tube in group P were significantly shorter than those in group C (P < 0.05). The postoperative serum IL-6 levels of patients in group P were significantly lower than those in group C at each time point (P < 0.05). Conclusions: Parecoxib effectively controls pain after PD. Prophylactic analgesia using parecoxib for up to 5 days after PD is safe, feasible, and can provide the same optimal pain control as opioids without adverse effects. Highlights: Regular use of parecoxib for 5 days after pancreaticoduodenectomy reduces the use of opioids. Regular use of parecoxib also reduces systemic inflammation. Parecoxib can be used to help to safely implement Enhanced Recovery After Surgery after PD.